Life Cycle Assessment Application of Circular Economy in Quail Farms through Utilization of Black Soldier Fly - Elida Novita; Ahmad Sa’id Khoirul Barri (Universitas Ibn Khaldun Bogor, 2025)
Quail farming plays a role in providing a source of animal protein for the community. However, farmers are often faced with the problem of high ration prices and the difficulty of handling waste. The circular economy model using BSF larvae has the potential to overcome these two problems. The utilization of BSF larvae in a circular economy has the potential as feed and is known as a decomposer of organic waste, including quail farm waste. However, as a process increases, energy consumption will also increase and increase the potential for greenhouse gas (GHG) emissions. Therefore, this study aims to assess the impact of global warming, production energy efficiency, and provide recommendations to produce a more efficient and environmentally friendly production process. One that can be used is the life cycle assessment (LCA) method which refers to the ISO 14040 standard. The LCA method has four stages in its method, namely: defining objectives and scope, inventory analysis, impact assessment, and interpretation followed by improvement. The results showed that through the application of a circular economy with the use of BSF larvae as a waste treatment organism, it was able to reduce GWP. Before the implementation of the circular economy, the GWP produced was 19.60 kg CO2eq. Then after the implementation of the circular economy, the first alternative GWP decreased to 10.78 kg CO2eq and in the second alternative, due to higher energy use, the resulting GWP increased to 31.73 kg CO2eq. Through the implementation of a circular economy, production energy efficiency is considered good, namely the 1st alternative NEV: 284.58 and NER: 1.59. Meanwhile, the second alternative resulted in NEV and NER which were smaller than the 1st alternative, with NEV: 156.90 and NER: 1.19. Whereas before the implementation of the circular economy NEV: -320.64 and NER: 0.12. Recommendations to produce more efficient and environmentally friendly production are: replacing the energy source of the drying process from LPG fuel with solar heat energy as an energy source in the drying process of BSF larvae.